(untitled) (Revista Cientifica Ingenio Magno, 2023)
Composite materials have a wide field of applications in different types of industries such as automotive, aeronautics, aerospace, transportation and military. Non-destructive evaluation, using ultrasound, plays an important role in the prevention of catastrophic failures in engineering components and structures during their entire operational life. This work presents the development of an experimental methodology for the generation, acquisition, processing, and interpretation of ultrasonic signals in composite materials through the implementation of a signal acquisition, processing and storage interface using the commercial software LabVIEW®. The use of the virtual instrument developed allows the monitoring and capture of signals by implementing different filters during the inspection. Finally, an analysis of the captured signals is shown using the Fast Fourier Transform, FFT, to determine the frequency components of the signal, implementing a function developed in MATLAB®.